Implikasi Pemberian Bantuan Hukum Oleh Dosen Pegawai Negeri Sipil sebagai Advokat Ditinjau dari Aspek Kemanfaatan Hukum: (Studi Kasus Putusan Mahkamah Konstitusi Nomor: 150/PUU-XXII/2024) - Yanuar Putra Erwin; Rasji (CV Rewang Rencang, 2024)
Lecturers as professional educators and scientists have a main task, one of which is to carry out community service. Community service is carried out as part of the Tridharma of College. One form of community service is by providing legal aid to the community, such as the advocate profession which can provide legal assistance in court or outside the court. The problem arose when the Law on Advocates prohibited civil servant lecturers from becoming and acting as advocates, meaning that civil servant lecturers were prohibited from carrying out the profession of advocates and acting as advocates. However, after the Constitutional Court Decision Number 150/PUU-XXII/2024, civil servant lecturers were finally able to act as advocates in providing free legal assistance to the community.